Gd-DTPA-Enhanced MR Imaging of Spinal Tumors - Parizel, Paul M.; Balériaux, Danielle; Rodesch, Georges; Segebarth, Christoph; Lalmand, Benjamin; Christophe, Catherine; Lemort, Marc; Haesendonck, Philippe; Niendorf, H. Peter; Flament-Durand, J.; Brotchi, Jacques (American Journal of Neuroradiology, 1989)
Forty-eight Gd-DTPA-enhanced MR examinations of the spine were performed in 40 patients referred for MR because of clinically suspected spinal tumor or for further evaluation of an expanded cord. The study group consisted of 32 patients with spinal tumors (seven ependymomas; seven astrocytomas; four hemangioblastomas; two arteriovenous malformations; two unidentified intramedullary neoplasms; four meningiomas; and single cases of metastatic breast carcinoma, cavernous hemangioma with associated hematomyelia, neurinoma, angiolipoma, drop metastasis from medulloblastoma, and epidermoid with diastematomyelia). In the remaining eight patients, other diagnoses were established: thoracic disk herniation (two patients), lumbosacral meningocele (one), syringomyelia secondary to arachnoiditis (four), and expanded cord secondary to gliotic tissue (one). All but two diagnoses were proved histologically by biopsy, surgery, or autopsy; in the two patients with arteriovenous malformations, the definitive diagnosis was made by spinal angiography. Contrast enhancement occurred in 30 of the 32 spinal tumors, and Gd-DTPA-enhanced T1-weighted images proved helpful in defining and outlining intra- and extramedullary spinal neoplasms. All ependymomas and astrocytomas (including low-grade astrocytomas) enhanced. In meningiomas, an immediate and uniform contrast uptake was demonstrated. Additional advantages of Gd-DTPA MR include the differentiation of solid tumor components vs syrinx or cyst or pseudotumoral areas of cord expansion, and the differentiation of residual or recurrent tumor from scar tissue in postoperative patients. Our results suggest that IV-injected Gd-DTPA improves MR sensitivity and specificity in the evaluation of spinal lesions.